2021
DOI: 10.1017/cjn.2021.206
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Intracortical Functions in Parkinson’s Disease with Rapid Eye Movement Sleep Behaviour Disorder

Abstract: Background: Rapid eye movement sleep behaviour disorder (RBD) is considered to be one of the most frequent and important prodromal symptoms of Parkinson’s disease (PD). We aimed to study the neurophysiological abnormalities in patients of PD-RBD and PD without RBD (PD-nRBD) using transcranial magnetic stimulation (TMS). Methods: Twenty patients each of PD-RBD and PD-nRBD were included in the study in addition to 20 age and gender-matched healthy controls. RBD was identified using the RBD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…Research has shown that clinical PD patients with RBD had more profound inhibition of SICI and lower intensity of ICF than those without RBD ( 18 ). This finding might lead to the thought that additional and widespread electrophysiological deficits would present when clinical PD is comorbid with RBD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that clinical PD patients with RBD had more profound inhibition of SICI and lower intensity of ICF than those without RBD ( 18 ). This finding might lead to the thought that additional and widespread electrophysiological deficits would present when clinical PD is comorbid with RBD.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with iRBD, the cortical excitability showed decreasing SICI and intracortical facilitation (ICF) intensity ( 15 , 16 ). However, limited reports compared the difference between clinical PD patients with and without RBD ( 17 , 18 ), and the cortical excitability changes in prodromal PD have not yet been well elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…RBD is one of the prodromal symptoms of PD. RBD showed visual hallucinations, dream enactments, muscle twitching during REM sleep, psychosis, autonomic disturbances, and dementia [ 57 ]. Abnormal dream enactments characterize RBD during REM sleep with activities such as punching, waving, swinging wildly, or jumping out of bed [ 77 ].…”
Section: Sleep Disturbances In Parkinson’s Diseasementioning
confidence: 99%
“…With the help of transcranial magnetic stimulation, Bhattacharya and co-workers evaluated neurophysiological abnormalities in PD patients with and without RBD. The PD-RBD patients showed significantly strong inhibition of intracortical facilitation, glutamatergic transmission, and enhanced GABAergic transmission [ 57 ].…”
Section: Evaluation Of Sleep Disordersmentioning
confidence: 99%
“… 110 Finally, another report has recently compared PD without and with RBD: an enhancement of GABA-mediated and a reduction of glutamine-mediated activity was found in PDRBD only, thus suggesting a distinctive physiopathological processes in these subjects. 111 …”
Section: Neurophysiological Biomarkers Of Neurodegeneration In Rbdmentioning
confidence: 99%